Tunica vaginalis flap for urethrocutaneous fistula repair after proximal and mid-shaft hypospadias surgery: A 12-year experience. Issue 5 (October 2018) - Pescheloche, Pierre; Parmentier, Benoit; Hor, Thevy; Chamond, Olivier; Chabaud, Maud; Irtan, Sabine; Audry, Georges
Summary: Introduction: Fistulas are a common complication of hypospadias surgery; they are more frequent after mid-shaft and posterior hypospadias repair. Surgical treatment of fistula still remains challenging with a significant failure rate. The basic principle is to add layers between skin and neourethra in order to decrease the incidence of recurrent urethrocutaneous fistula (UCF). We report our experience of UCF repair using a vascularized tunica vaginalis flap (TVF) after posterior and mid-shaft hypospadias surgery. Material and methods: A retrospective review of all patients operated on using TVF for UCF in our institution between December 2005 and July 2017 was performed. Results: Among 36 cases, TVF was used at a first attempt in 22 patients; 14 children had a prior attempt to close the fistula, and four of them had two surgeries before TVF repair. UCF was respectively penoscrotal ( n  = 3, 8%), posterior ( n  = 19, 53%), midshaft ( n  = 9, 25%) and anterior ( n  = 5, 14%). The size of the fistula was more than 5 mm in 26 patients. The UCF was treated successfully in every case after one single procedure. In the three children with two fistulas, both fistulas were successfully treated by the same TVF. After an average follow-up time of 45 months there was no recurrence of the initial UCF. In four cases of undescended testis, it was possible to dissect the flap through an inguinal incision and perform an orchydopexy in the same time. One patient presented a testicular atrophy after undescended testis surgery. Discussion: Area review of published series shows excellent results in UCF repair including recurrent fistula (Table). TVF can aspire to some advantages with regard to a dartos flap (DF). First of all, a nearly 2.5-fold lower incidence of fistula after fistula repair with TVF than with DF (5.1% vs. 12.2%) has been shown. Secondly, TVF allows treating multiple fistulas, and can also be brought to the anterior part of the penis until the balano preputial furrow, allowing curing anterior fistula. Furthermore, it doesn't lead to aesthetic complications such as penile rotation or distal skin necrosis, which can occur during DF procedures. Conclusion: TVF is a simple and reproductive technique for UCF repair, with a high success rate. The risk of testicular atrophy has to be considered in case of associated undescended testis surgery, and careful attention must be given to the TVF dissection. This technique should be considered as first choice treatment for any UCF. Table Literature review. Authors Date Cases ( n ) Including recurrent UCF Average length of urethral stent (days) Average follow-up (months) Fistula recurrence after TVF Landau et al. 2003 14 14 (100%) 5.5 44 0% Routh et al. 2006 16 12 (75%) 7 18 0% Xie'eryazidan et al. 2009 26 ? ? ? 15% Muruganandham et al. 2010 13 4 (31%) 7–10 28 0% Kadian et al. 2011 14 14 (100%) 10 ? (maximum 2 years) 0% Pescheloche et al. 2017 36 14 (39%) 7 45 0%